LITERATURE REVIEW : Cost Effective Analysis of Sitagliptin for the Treatment of Diabetes Mellitus Type 2 - Vidiani, Anak Agung Pradnya Paramitha; Puspitaningrum, Anisa Nova; Girsang, Valentina; Adrianto, Madyo (Science and Community Pharmacy Journal, 2024)
Diabetes mellitus (DM) is a chronic disease characterized by increased glucose levels in the blood. The prevalence of type 2 DM is currently increasing. In pharmacological treatment, metformin is the first-line oral therapy for most patients with type 2 diabetes. Therapy with targeted incretin has been shown to stimulate glucose-dependent insulin secretion, reduce glucagon secretion, improve beta cell function, slow gastric emptying, increase satiety, reduce appetite, and provide general benefits beyond the pancreas. Search for scientific articles by utilizing internet searches through Google Scholar and PubMed. Using keywords related to "Cost Effective Analysis", "Diabetes Mellitus type 2", "Sitagliptine" with Boolean operator "AND". Sitagliptin is less cost-effective when compared to liraglutide. Sitagliptin is the first agent of the DPP-4 inhibitor with other substances following soon after. The evaluation shows that the prevention of complications in patients with type 2 diabetes and cardiovascular disease (CVD) in the SGLT2 inhibitor group is more recommended, namely empaglifozin as the second line compared to sitagliptin.